2014
DOI: 10.1007/s10661-014-3889-0
|View full text |Cite
|
Sign up to set email alerts
|

Storm water contamination and its effect on the quality of urban surface waters

Abstract: We studied the effect of storm water drained by the sewerage system and discharged into a river and a small reservoir, on the example of five catchments located within the boundaries of the city of Poznań (Poland). These catchments differed both in terms of their surface area and land use (single- and multi-family housing, industrial areas). The aim of the analyses was to explain to what extent pollutants found in storm water runoff from the studied catchments affected the quality of surface waters and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 27 publications
(30 reference statements)
3
34
0
Order By: Relevance
“…The biogeochemical fingerprint of urban land cover on stormwater quality is undisputable, as the concentrations and loads increased with urban intensity. The studied concentrations (except SO 4 ) exhibited positive covariation with urban land cover type and negative relationships with vegetation coverage (in agreement with Schoonover et al, ; Fitzpatrick et al, ), which has been shown to trap substances effectively (Barałkiewicz et al, ). Valtanen et al () identified similar association between watershed perviousness and spatial variation of total nutrients, TDS, and metal concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…The biogeochemical fingerprint of urban land cover on stormwater quality is undisputable, as the concentrations and loads increased with urban intensity. The studied concentrations (except SO 4 ) exhibited positive covariation with urban land cover type and negative relationships with vegetation coverage (in agreement with Schoonover et al, ; Fitzpatrick et al, ), which has been shown to trap substances effectively (Barałkiewicz et al, ). Valtanen et al () identified similar association between watershed perviousness and spatial variation of total nutrients, TDS, and metal concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…The average concentrations of nitrate-nitrogen (NO 3 --N), ammonium-nitrogen (NH 4 + -N), total N, molybdate-reactive P, total P, and suspended matter in the runoff of Nanjing City, China were 8, 2, 6, 15, 6 and 4 times greater than those of the forested watershed, respectively. Barałkiewicz et al (2014) observed that the Cd, Zn, Pb, and Co in the runoff from the largest impervious area had the strongest toxic effect on aquatic organisms. In the city areas, soil loses almost all of its inherent physical and chemical ability to filter, absorb and purify water.…”
Section: Water Qualitymentioning
confidence: 94%
“…These areas are frequently lack adequate sewerage, having only septic tanks which may fail to work properly, thus most of the wastewater infiltrates through the ground into the lake (Hall and Härkönen, 2006). Such usage brings about an acceleration of eutrophication and the aquatic ecosystem becomes extremely degraded (Zuccarini et al, 2011;Barałkiewicz et al, 2014;Grochowska et al, 2015). The lake can no longer be used recreationally and most of the other ecosystem services are also lost (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%